Cancer acidity and hypertonicity contribute to dysfunction of tumor-associated dendritic cells: Potential Impact on Antigen Cross-Presentation Machinery - Burgdorf, Sven; Porubský, Štefan; Marx, Alexander; Popovic, Zoran V. (Cancers, 2020)
Macrophages (MΦ) and dendritic cells (DC), major players of the mononuclear phagocyte system (MoPh), are potent antigen presenting cells that steadily sense and respond to signals from the surrounding microenvironment, leading to either immunogenic or tolerogenic outcomes. Next to classical MHC-I/MHC-II antigen-presentation pathways described in the vast majority of cell types, a subset of MoPh (CD8+, XCR1+, CLEC9A+, BDCA3+ conventional DCs in human) is endowed with a high competence to cross-present external (engulfed) antigens on MHC-I molecules to CD8+ T-cells. This exceptional DC function is thought to be a crucial crossroad in cytotoxic antitumor immunity and has been extensively studied in the past decades. Biophysical and biochemical fingerprints of tumor micromilieus show significant spatiotemporal differences in comparison to non-neoplastic tissue. In tumors, low pH (mainly due to extracellular lactate accumulation via the Warburg effect and via glutaminolysis) and high oncotic and osmotic pressure (resulting from tumor debris, increased extracellular matrix components but in part also triggered by nutritive aspects) are—despite fluctuations and difficulties in measurement—likely the most constant general hallmarks of tumor microenvironment. Here, we focus on the influence of acidic and hypertonic micromilieu on the capacity of DCs to cross-present tumor-specific antigens. We discuss complex and in part controversial scientific data on the interference of these factors with to date reported mechanisms of antigen uptake, processing and cross-presentation, and we highlight their potential role in cancer immune escape and poor clinical response to DC vaccines.
Gesehen am 04.12.2025